ETMM-04. AURKA INHIBITION REPROGRAMS METABOLISM AND IS SYNTHETICALLY LETHAL WITH FATTY ACID OXIDATION INHIBITION IN GLIOBLASTOMA MODEL SYSTEMS. (25th March 2021) - Nguyen, Trang; Shu, Chang; Shang, Enyuan; Mela, Angeliki; Humala, Nelson; Mahajan, Aayushi; Akman, Hasan; Quinzii, Catarina; Zhang, Guoan; Westhof, Mike-Andrew; Karpel-Massler, Georg; Bruce, Jeffrey; et al.
Abstract: Aurora kinase A (AURKA) has emerged as a viable drug target for glioblastoma (GBM), the most common malignant primary brain tumor in adults with a life expectancy of 12–15 months. However, resistance to therapy remains a critical issue, which partially may be driven by reprogramming of metabolism. By integration of transcriptome, chromatin immunoprecipitation with sequencing (CHIP-seq.), assay for transposase-accessible chromatin with sequencing (ATAC-seq.), proteomic and metabolite screening followed by carbon tracing (U- 13 C-Glucose, U- 13 C-Glutamine and U- 13 C-Palmitic acid) and extracellular flux analysis we provided evidence that genetic (shRNA and CRISPR/Cas9) and pharmacological (Alisertib) AURKA inhibition elicited substantial metabolic reprogramming supported in part by inhibition of MYC targets and concomitant activation of PPARA signaling. While glycolysis was suppressed by AURKA inhibition, we noted a compensatory increase in oxygen consumption rate fueled by enhanced fatty acid oxidation (FAO). Whereas interference with AURKA elicited a suppression of c-Myc, we detected an upregulation of PGC1A, a master regulator of oxidative metabolism. Silencing of PGC1A reversed AURKAi mediated metabolic reprogramming and sensitized GBM cells to AURKAi driven reduction of cellular viability. Chromatin immunoprecipitation experiments showed binding of c-Myc to the promoter region of PGC1A, which is abrogated by AURKA inhibition and in turn unleashed PGC1A expression. Consistently, ATAC-seq. confirmed higher accessibility of a MYC binding region within the PGC1A promoter, suggesting that MYC acts as a repressor of PGC1A. Combining alisertib with inhibitors of FAO or the electron transport chain exerted substantial synergistic growth inhibition in PDX lines in vitro and extension of overall survival in orthotopic GBM PDX models without induction of toxicity in normal tissue. In summary, these findings support that simultaneous targeting of oxidative energy metabolism and AURKAi might be a potential novel therapy against GBM.